Disrupting Interactions Between β‐Catenin and Activating TCFs Reconstitutes Ground State Pluripotency in Mouse Embryonic Stem Cells. (15th June 2017) - Saj, Abil; Chatterjee, Sujash S.; Zhu, Bowen; Cukuroglu, Engin; Gocha, Tenzin; Zhang, Xiaoqian; Göke, Jonathan; DasGupta, Ramanuj
Abstract: The 2i‐media, composed of two small molecule inhibitors (PD0325901 and CHIR99021) against MEK and GSK3‐kinases, respectively, is known to establish naïve ground state pluripotency in mouse embryonic stem cells (mESCs). These inhibitors block MEK‐mediated differentiation, while driving β‐catenin dependent de‐repression of pluripotency promoting targets. However, accumulating evidence suggest that β‐catenin's association with activating TCFs (TCF7 and TCF7L2) can induce expression of several lineage‐specific prodifferentiation genes. We posited that CHIR‐induced upregulation of β‐catenin levels could therefore compromise the stability of the naïve state in long‐term cultures. Here, we investigated whether replacing CHIR with iCRT3, a small molecule that abrogates β‐catenin–TCF interaction, can still retain ground state pluripotency in mESCs. Our data suggests that iCRT3 + PD mediated coinhibition of MEK and β‐catenin/TCF‐dependent transcriptional activity over multiple passages significantly reduces expression of differentiation markers, as compared to 2i. Furthermore, the ability to efficiently contribute toward chimera generation and germline transmission suggests that the inhibition of β‐catenin's TCF‐dependent transcriptional activity, independent of its protein expression level, retains the naïve ground state pluripotency in mESCs. Additionally, growth medium containing iCRT3 + PD can provide an alternative to 2i as a stable culture method. Stem Cells 2017;35:1924–1933 Abstract : Model depicting the differences between 2i and iCRT3 + PD media in the regulation of mESC pluripotency. In 2i media, CHIR‐mediated increase in β‐catenin level promotes its association with both pluripotency promoting protein complexes such as TCF7L1 and Pou5f1. Concurrently, the excess β‐catenin may associate with transcription activating TCFs, such as TCF7 and promote the expression of pro‐differentiation genes. Conversely, in the iCRT3 + PD culture condition iCRT3 abrogates the interaction between β‐catenin and TCF7 thereby decreasing the expression of differentiation promoting genes. However the endogenous levels of β‐catenin in iCRT3 + PD remains adequate to associate with pluripotency promoting protein complexes. PD, in both culture conditions inhibits the MEK mediated differentiation.